Cesarean section rates according to the Robson Classification and its association with adequacy levels of prenatal care: a cross-sectional hospital-based study in Brazil - Veridiana Monteiro Ramos Piva; Verena Voget; Luciana Bertoldi Nucci (BMC, 2023)
Abstract Background The rate of Cesarean section (CS) deliveries has been increasing worldwide for decades. Brazil exhibits high rates of patient-requested CS deliveries. Prenatal care is essential for reducing and preventing maternal and child morbidity and mortality, ensuring women's health and well-being. The aim of this study was to verify the association between the level of prenatal care, as measured by the Kotelchuck (APNCU - Adequacy of the prenatal care utilization) index and CS rates. Methods We conducted a cross-sectional study based on data from routine hospital digital records and federal public health system databases (2014-2017). We performed descriptive analyses, prepared Robson Classification Report tables, and estimated the CS rate for the relevant Robson groups across distinct levels of prenatal care. Our analysis also considered the payment source for each childbirth - either public healthcare or private health insurers - and maternal sociodemographic data. Results CS rate by level of access to prenatal care was 80.0% for no care, 45.2% for inadequate, 44.2% for intermediate, 43.0% for adequate, and 50.5% for the adequate plus category. No statistically significant associations were found between the adequacy of prenatal care and the rate of cesarean sections in any of the most relevant Robson groups, across both public (n = 7,359) and private healthcare (n = 1,551) deliveries. Conclusion Access to prenatal care, according to the trimester in which prenatal care was initiated and the number of prenatal visits, was not associated with the cesarean section rate, suggesting that factors that assess the quality of prenatal care, not simply adequacy of access, should be investigated.